1991
DOI: 10.1007/bf02208686
|View full text |Cite
|
Sign up to set email alerts
|

Acquired hyperostosis syndrome: Spectrum of manifestations at the sternocostoclavicular region. Radiologic evaluation of 34 cases

Abstract: Thirty-four patients with chest wall hyperostosis, a condition which has been designated by various terms in the literature were evaluated radiologically. We prefer the name acquired hyperostosis syndrome (AHS), which we categorize into the complete, incomplete and possible form. In complete AHS, sternocostoclavicular hyperostosis is associated with axial and/or peripheral (endosteal, periosteal, enthesopathic, metaplastic) hyperostosis and with psoriasiform or acneform dermatosis. In addition, these three man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 42 publications
1
26
0
3
Order By: Relevance
“…Clinical manifestations SCCH very infrequently may be asymptomatic with radiographic findings only [Katz et al 1989] but in most cases the disorder presents with pain and palpable tenderness in the sternoclavicular region [Dihlmann and Dihlmann, 1991;Chigira and Shimizu, 1989]. Local swelling and warmth is almost always present [Chigira and Shimizu, 1989].…”
Section: Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical manifestations SCCH very infrequently may be asymptomatic with radiographic findings only [Katz et al 1989] but in most cases the disorder presents with pain and palpable tenderness in the sternoclavicular region [Dihlmann and Dihlmann, 1991;Chigira and Shimizu, 1989]. Local swelling and warmth is almost always present [Chigira and Shimizu, 1989].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Tests for rheumatoid factor and other immunological tests are usually negative [Economou et al 1993]. Although patients of European descent may demonstrate a slightly increased prevalence of HLA-B27 positivity, no clear relationship to SCCH has been demonstrated [Dihlmann and Dihlmann, 1991].…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Most reports have suggested that sterno-costo-clavicular hyperostosis or nonspecific osteitis is a significant aetiology of PPP or, at least, is an important factor contributing to the cutaneous manifestations [4,5,13,15,16,23,31]. This osseo-arthro-cutaneous syndrome shows unique clinical manifestations which may correlate with each other during its lengthy course [8,9,14,18].…”
Section: Introductionmentioning
confidence: 99%